2021
DOI: 10.1002/cncr.34048
|View full text |Cite
|
Sign up to set email alerts
|

Perceived financial decline related to breast reconstruction following mastectomy in a diverse population‐based cohort

Abstract: Background Despite mandated insurance coverage for breast reconstruction following mastectomy, health care costs are increasingly passed on to women through cost‐sharing arrangements and high‐deductible health plans. In this population‐based study, the authors assessed perceived financial and employment declines related to breast reconstruction following mastectomy. Methods Women with early‐stage breast cancer (stages 0‐II) diagnosed between July 2013 and May 2015 who underwent mastectomy were identified throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(46 reference statements)
1
4
0
Order By: Relevance
“…That CHE and employment outcomes are affected by annual household income is consistent with previous studies on FT among BC patients ( 2 , 27 , 36 , 37 ). Other studies have even demonstrated an association between income and survival after treatment for cancer ( 38 ).…”
Section: Discussionsupporting
confidence: 90%
“…That CHE and employment outcomes are affected by annual household income is consistent with previous studies on FT among BC patients ( 2 , 27 , 36 , 37 ). Other studies have even demonstrated an association between income and survival after treatment for cancer ( 38 ).…”
Section: Discussionsupporting
confidence: 90%
“…Outof-pocket costs are higher after breast reconstruction than after mastectomy alone, and reconstruction has been found to be independently associated with a perceived decline in financial status. 1 This decline in financial status was attributed in part to the cumulative financial and time burden of procedures and postoperative complications as 1 in 10 women undergo more than three major operative procedures directly related to breast reconstruction. 11 Breast reconstruction is a highly personalized process which takes into consideration a multitude of patient factors and values in the process of shared decision making.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, many barriers to surgeoninitiated cost-of-care discussions have been cited, including surgeons believing it is not their role, insufficient knowledge or resources, a perceived inability to help with costs, inadequate time, and specific to plastic surgeons, some concern that discussing costs may impact the treatment recommendations and outcomes that patients receive. 1,22,23 Though many of these concerns may be unfounded (discussions of health care expenses in the oncology clinic have been found to have a median duration of 33 seconds), plastic surgeons may not be the optimal team member to engage in these discussions. 24 Moreover, the results of this study indicate that a greater percentage of women would prefer discussions about the potential costs of breast reconstruction from a member of the surgical team rather than the plastic surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of breast cancer patients that had or had not undergone reconstruction reported significantly higher out-of-pocket costs and financial stress in reconstructed patients. 18 Complications during breast reconstruction add to the burden. Patients undergoing a second attempt after failure have higher complication rates and repeated failures.…”
Section: Introductionmentioning
confidence: 99%